O stylu medialnym jako odmianie współczesnej polszczyzny = On the media style as a variety of modern Polish - Wojtak, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author returns to the issues of differentiation of the Polish language and the question of distinguishing the variety associated with the media. After presenting the whole range of positions of various linguists, while paying attention to the terminological polilexia and the basic differences in the way of grasping these issues, she presents her own concept of the media style. She proposes the cultural and descriptive approach to this phenomenon (and not differential). The author postulates that the relationship between language varieties should be viewed multidimensionally. She also points to the possibility of different interpretations of the issue of identity of language varieties.
Keywords: media; prasa; odmiana języka; styl językowy; odmiana medialna; styl medialny; press; linguistic varieties; language style; media variety; media style